Implementation of Electricity Competition Framework with Economic Dispatch Direct Method - Hermagasantos Zein; Yusra Sabri; Ali Mashar (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2012)
Technically, electricity business under competition structure is more complex than that of vertically integrated one. A competition framework has to be designed to implement bidding strategies with electrical calculations as quickly as possible (not more than 15 minets). This paper proposes a competition framework with the electric calculations, where a bilateral contract has been accommodated. Optimal energy price in the paper is calculated based on direct method of economic dispatch to obtain the result very quickly. The proposed method has been simulated to a 4-bus system. The simulation results show that the method works well and complies with the expectation. Therefore, electric power business under competition structure can be well realized by the proposed method.